Fiscal Policy, Growth and Competitiveness in EMU: Evidence from Portugal and Greece - Psychalis, Marios; Gournas, Panagiotis; Grigorakou, Nagia; Dimitrakopoulos, Petros; Stivachtis, George (International Journal of Economics and Financial Issues, 2020)
This paper aims at examining whether reforms in EU economic and fiscal governance between the period starting from 2010 and ending on 2018 have increased the Gross Domestic Product growth rate in Greece and Portugal. Reforms occurred, such as “Six Pack”, “Two Pack”, the “Fiscal Compact”, and the “Euro Plus Pact”, have focused on fiscal consolidation and competitiveness improvement; in other words, during the aforementioned time period, EMU concentrated on the improvement of internal as well as external imbalances. Moreover, the present paper assesses the international competitiveness through the prism of two main indicators: Unit Labour Cost and Current Account Balance. It seems that the literature is not crystal clear on the relationship between debt and the fiscal policy on the one side, competitiveness and growth from the other side. The findings of the paper may be of great assistance to policy makers on growth, competitiveness and fiscal policy, as they highlight the relationship between economic stability, entrepreneurship and growth. The herein below presented results demonstrate that there is, indeed, a strong relationship between fiscal consolidation and growth, while the relationship between public debt, Unit Labour Cost, Current Account Balance and growth remains blurred. Keywords: Fiscal reforms, Entrepreneurship, Competitiveness, Economic Policy in EMU JEL Classifications: H30, H60, F15 DOI: https://doi.org/10.32479/ijefi.9889